2016
DOI: 10.18632/oncotarget.7028
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum and risk stratification of intermediate-risk acute myeloid leukemia patients based on next-generation sequencing

Abstract: Intermediate-risk acute myeloid leukemia (IR-AML), which accounts for a substantial number of AML cases, is highly heterogeneous. Although several mutations have been identified, the heterogeneity of AML is uncertain because novel mutations have yet to be discovered. Here we applied next generation sequencing (NGS) platform to screen mutational hotspots in 410 genes relevant to hematological malignancy. IR-AML samples (N=95) were sequenced by Illumina Hiseq and mutations in 101 genes were identified. Only seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 54 publications
6
26
2
Order By: Relevance
“…About 86.8% (132 cases) of our patients were assigned to M2/M4/M5 subtypes, and five genes including NPM1 , CEBPAbi , GATA2 , RUNX1 , and DNMT3A exhibited a specificity in mutation distribution in regard to FAB subtypes (Figure a and b). NPM1 and DNMT3A mutations were mostly involved in the M4 and M5 subtypes (31.7%, 32/101 and 28.7%, 29/101), and this trend was consistent with the Western and Asian reports (20.3% to 56.0% for NPM1 mut and 20.3% to 43.0% for DNMT3A mut ) . However, the high mutation rates of CEBPAbi (58.1%) and GATA2 (35.5%) genes constituted the specific feature in M2 subtype in our cohort, which was not reported before.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…About 86.8% (132 cases) of our patients were assigned to M2/M4/M5 subtypes, and five genes including NPM1 , CEBPAbi , GATA2 , RUNX1 , and DNMT3A exhibited a specificity in mutation distribution in regard to FAB subtypes (Figure a and b). NPM1 and DNMT3A mutations were mostly involved in the M4 and M5 subtypes (31.7%, 32/101 and 28.7%, 29/101), and this trend was consistent with the Western and Asian reports (20.3% to 56.0% for NPM1 mut and 20.3% to 43.0% for DNMT3A mut ) . However, the high mutation rates of CEBPAbi (58.1%) and GATA2 (35.5%) genes constituted the specific feature in M2 subtype in our cohort, which was not reported before.…”
Section: Resultssupporting
confidence: 87%
“…Differences in mutation frequencies between particular genes and in cytomorphology were also observed. DNMT3A and NPM1 mutations were more involved in M4 and M5 subtypes as in the most reports in literature . However, the specific feature of high mutation rates of CEBPA and GATA2 genes in M2 subtype, which may also characterize Chinese CN‐AML, was first noted in our study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Wang et al [36] reported high mutation rates (>10%) in CEBPA, NPM1, DNMT3A, FLT3-ITD, NRAS, IDH2 and WT1 . Kihara et al [37] reported high mutation rates of FLT3, NPM1, CEBPA, DNMT3A and KIT mutations in Japanese patients with AML.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity to screen mutational hotspots in different target genes by target re-sequencing is biologically meaningful and reveals new evidences regarding the risk stratification of the patients. In this regard, it was observed that the genomic profile of leukemic clones may significantly change from diagnosis to relapse showing the emergence of clones that are more difficult to eradicate [5][6][7]. In the next future, these technologies will be commonly available, but currently the great majority of hematological centers do not have the opportunity of adopting them into clinical practice.…”
Section: Short Communicationmentioning
confidence: 99%